Survey of parasitoids of whiteflies (Homoptera: Aleyrodidae) in cassava growing regions of Colombia and Ecuador - Trujillo García, H.E.; Arias, B.; Guerrero, J.M.; Hernández, P.; Bellotti, Anthony C.; Pena, J.E. (Florida Entomological Society, 2004)
A survey for parasitoids of the whiteflies, Bemisia tuberculata Bondar, Trialeurodes variabilis Quantaince, T. vaporariorum (Westwood), Aleurotrachelus socialis Bondar, Tetraleurodes sp., Aleuroglandulus malangae Russell and Aleurodicus sp., was conducted in 6 cassava growing regions of Colombia and Ecuador. In Colombia, the degree of infestation was predominantly high (>29 whiteflies/cm 2 ) for A. socialis , B. tuberculata and T. variabilis in all cassava growing regions. In Ecuador, levels of infestations were high for Aleurodicus sp., A. socialis , B. tuberculata , Tetraleurodes sp. in the coastal region, and for T. vaporariorum in the Highlands. The parasitoid fauna of the whiteflies appeared to be more diverse in Colombia than in Ecuador. Eleven species of parasitoids representing 5 genera, 4 families and two superfamilies, as well as 1 hyperparasitoid, were collected from the cassava growing regions of Colombia and 4 species were collected from Ecuador. The parasitoids, Amitus macgowni Evans and Castillo, Encarsia sp., E. hispida De Santis, E. pergandiella Howard, E. bellottii Evans and Castillo, E. luteola group, E. sophia (Girault and Dodd), E. strenua group, Eretmocerus sp., Metaphycus sp. and Euderomphale sp., were collected. There were notable differences in parasitism among the different geographic regions and whitefly species. In general, Eretmocerus was the dominant genus in Colombia and Ecuador, followed by Encarsia sp. We found A. macgowni in regions characterized by high temperatures and bimodal rainfall. Percent parasitism per region surveyed ranged from 3 to 25% in Colombia and from 12 to 21% in Ecuador.